Development of learning materials reading understanding using CIRC in four primary schools - Weni Aulia; Ardipal Ardipal; Darnis Arief (International Conferences on Educational, Social Sciences and Technology)
This research is motivated by teaching materials that are used less interest of students to read and not yet contain reading stage (pre-reading, reading and post-reading). The purpose of developing this instructional material is to produce a reading material that is valid, practical, and effective. The type of this research is development research using 4-D model. Based on the validity test obtained percentage of RPP by the expert validator 91.6% and 90.0% practitioner validator. Percentage of teaching materials by 90.6% expert validator and 89.9% practitioner validator. Practicality test of the implementation of RPP obtained percentage of 92.7%. Assessment of teacher responses obtained 93% and assessment of the response learners obtained 89.2% percentage The effectiveness of learning tools learners obtained percentage 81.6%. Assessment of comprehension reading process obtained 75.5% percentage. Based on these results, learning materials to read the understanding using the CIRC model can already be declared valid, practical, and effective.